Plasma lncRNA GAS8-AS1 as a Potential Biomarker of Papillary Thyroid Carcinoma in Chinese Patients - Dongxue Zhang; Xin Liu; Bojun Wei; Guoliang Qiao; Tao Jiang; Zhenwen Chen (International Journal of Endocrinology)
Background. Long noncoding RNAs (lncRNAs) were recently shown to have potential in the diagnosis and prognosis for numerous cancers. lncRNA GAS8-AS1 is decreased in papillary thyroid cancer (PTC) tissue, but its plasma expression and clinical value in patients with PTC remain unknown. Materials and Methods. We investigated the expression profile of plasma GAS8-AS1 in 97 patients with PTC and 39 patients with nodular goiter by quantitative real-time polymerase chain reaction. Results. GAS8-AS1 expression in plasma was downregulated in patients with PTC in comparison with those in nodular goiters (P<0.001). A low level of plasma GAS8-AS1 expression was correlated with lymph node metastasis (LNM) (P<0.001). Multivariate analysis showed that a reduced GAS8-AS1 level in plasma was associated with LNM (P<0.05). The area under the receiver operating characteristic curve for GAS8-AS1 was 0.746 in LNM prediction (P<0.001). Conclusion. The present study indicates that circulating GAS8-AS1 is a potential biomarker for PTC diagnosis and LNM prediction.